Education And Pedagogy - Ashurov Jasur Djurayevich (Zien Journals, 2021)
The term pedagogy (gr. 'Paîs', paída - child, gr. 'Ágō', gogos - leader) is ancient and is derived from the Greek word "paydogogos", which means "child leader". Historical sources show that in ancient Greece, slaves were called "pedagogues" (tutors), ie educators who traveled, cared for, and taught military skills to their master's children. Later, people who were specially trained and trained in pedagogy were called pedagogues
Keywords: digital pedagogy; information and communication technologies